CCRL2 Modulates Physiological and Pathological Angiogenesis During Retinal Development - Ben Dhaou, Cyrine; Del Prete, Annalisa; Sozzani, Silvano; Parmentier, Marc (Frontiers in Cell and Developmental Biology, 2021)
Chemerin is a multifunctional protein involved in the regulation of inflammation, metabolism, and tumorigenesis. It binds to three receptors, CMKLR1, GPR1 and CCRL2. CMKLR1 is a fully functional receptor mediating most of the known activities of chemerin. CCRL2 does not seem to couple to any intracellular signaling pathway and is presently considered as an atypical receptor able to present the protein to cells expressing CMKLR1. CCRL2 is expressed by many cell types including leukocyte subsets and endothelial cells, and its expression is strongly upregulated by inflammatory stimuli. We recently reported that chemerin can negatively regulate the angiogenesis process, including during the development of the vascular network in mouse retina. The role of CCRL2 in angiogenesis was unexplored so far. In the present work, we demonstrate that mice lacking CCRL2 exhibit a lower density of vessels in the developing retina and this phenotype persists in adulthood, in a CMKLR1-dependent manner. Vascular sprouting was not affected, while vessel pruning, and endothelial cell apoptosis were increased. Pathological angiogenesis was also reduced in CCRL2-/- mice a model of oxygen-induced retinopathy. The phenotype closely mimics that of mice overexpressing chemerin, and the concentration of chemerin was found elevated in the blood of newborn mice, when the retinal vasculature develops. CCRL2 appears therefore to regulate the distribution and concentration of chemerin in organs, regulating thereby its bioactivity.